Methodological strategy to develop the state of the art as a product of educative research (Praxis Educativa, 2019)
Elaborating the state of the art represents an indispensable investigative process to establish a theoretical and methodological position that supports the development of a scientific investigation. In this document a proposal is presented to prepare the state of the art starting from the analysis of its conceptualization, also the moments that must be followed to develop this activity in the investigative process are explored. To achieve this, an investigation was carried out using a qualitative and interpretative design of documentary type. The result represents a computer scheme that can help consolidate the state of the art as a product of scientific research of an analytical-interpretative nature categorized into five moments 1) seed, 2) approximation to the object of study, 3) context and inventory, 4) analytical, and 5) interpretive.
Keywords: methodology; research.